Commodification of Celebrities in the 2024 General Election Contestation (2023)
General Election (GE) often becomes a complex political arena filled with strategies to influence public opinion. In recent years, there has been an interesting trend where celebrities actively engage in politics and run as legislative candidates. This phenomenon creates a new dynamic in politics known as celebrity commodification, figures that easily capture public attention. Their popularity in the entertainment industry gives them the confidence to venture into the realm of elected representatives. Famous celebrities from the fields of entertainment, sports, and media are utilized by political parties to boost their popularity and garner support from the public or the electorate in the democratic process. The phenomenon of celebrities running as legislative candidates and joining political parties, in the perspective of commodification, is discussed in relation to three aspects: the character of the celebrities, party branding, and the public as political consumers